Metodologia de projeto otimizado de filtros de entrada e saída de fontes ininterruptas de energia: volume, perdas e tempo de vida - Bolsi, Pedro Cerutti (2024)
In this work are developed design methodologies for LCL and LC filters, considering their impact on the entire system. The proposed methodology seeks, through a parametric sweep, to obtain the optimal design points for the efficiency, volume, and lifetime of the capacitors of the circuit. To this end, the methodology has two stages. The first consists of carrying out the parametric design of the filters, in which a scan of design inputs is carried out, delimited by the normative and operating restrictions of the converter. Using the proposed strategy, different combinations of L-C-L and L-C that meet the normative restrictions are raised. The second stage consists of designing the filter components, determining their construction using different technologies. Since the parametric sweep of the filter design inputs influences the rest of the system through changes in the harmonic content (current ripple), the losses and lifetime of the DC bus capacitors are determined, the losses in the semiconductors of the converters under analysis are estimated, and the design of the heat sinks is made. Finally, results are analyzed for filter designs that result in the lowest system volume, highest efficiency, and/or longest capacitor lifetime. The design procedures for each part of the power system are presented, as well as the models used in the design of the inductors, and in the estimation of losses, temperature and lifetime. With the proposed methodology, a case study of a 10 kVA three-phase four-wire uninterruptible power supply is developed, analyzing the possibility of constructing the inductors with three diferent magnetic material technologies (non grain oriented silicon steel, IP6 ferrite, Kool Mμ), with different geometries (EE and Toroid), and considering two capacitor technologies for the system. The results demonstrate how, using the proposed design methodology, the characteristics of each technology influence the final result, making it possible to determine the best design point for the LCL and LC filters.